Radiation-induced dysphagia and life-threatening stridor in nasopharyngeal carcinoma - Santosh Kumar Swain; Smrutipragnya Samal (Wolters Kluwer Medknow Publications, 2021)
Radiotherapy plays an important role in the treatment for head and neck cancer. The radiation to the head and neck region can lead to a rare long-term swallowing and breathing defect by causing stenosis at the pharynx which reduces the quality of life. We are presenting a case of radiation-induced severe pharyngeal stenosis in a 44-year-old female diagnosed with nasopharyngeal carcinoma. Nasopharyngeal carcinoma is a rare variety of the cancer where radiation therapy is the treatment of choice because of its high radiosensitivity. Radiation-induced dysphagia may occur due to structural, mechanical, and neurological deficits. Although radiotherapy has a promising outcome in nasopharyngeal carcinoma, complications around the irradiation areas are inevitable and lead to compromised quality of life. Although there is no effective treatment option available for pharyngeal stenosis, many supportive, restorative, and palliative treatments are available under different clinical situations. Here, we report a case of postradiation-induced pharyngeal stenosis presenting with dysphagia and stridor that underwent treatment with pharyngeal dilation with coblation.